Perspectives on athlete-centered coaching - Pill, Shane (London Routledge, Taylor & Francis Group, 2018)
"Underpinned by a philosophy of empowerment, athlete-centred approaches to coaching are defined by a style that promotes learning through ownership, responsibility, initiative and awareness. Perspectives on Athlete-Centred Coaching offers an in-depth theoretical examination of player-focused coaching models, and provides professional guidance for practising coaches. Written by a cast of world-leading scholars and practitioners, and offering a breadth of approaches to, and critiques of, the application of athlete-centred coaching, the book covers topics including: - athlete-centered coaching and holistic development - coaching tactical creativity - athlete-centred coaching in disability sport - team culture and athlete-centred coaching - developing thinking players through Game Sense coaching - supporting athlete wellbeing - athlete-centred coaching and teaching games for understanding - athlete-centred coaching in masters sport Based on the latest research and offering the most comprehensive enquiry into this central area of coaching theory, Perspectives on Athlete-Centred Coaching is important reading for any students and lecturers of sports coaching or physical education, and practising coaches across any sport"-- Provided by publisher.
Athlete-centred coaching : extending the possibilities of a holistic and process-oriented model to athlete development -- An athlete-centred approach to enhance thriving within athletes and coaches -- Coaching tactical creativity in team sports -- Athlete-centred coaching in disability sport : a critical perspective -- Team culture and athlete-centred coaching -- The importance of context in athlete-centred coaching -- Developing athlete-centred coaching in high performance field hockey -- Developing thinking players : a coach's experience with game sense coaching -- Supporting wellbeing : athlete transitions through elite to sub-elite sport -- Body in movement : better measurements for better coaching -- Athlete-centred coaching and teaching games for understanding - not quite the perfect match -- Athlete-centred coaching for individual sports -- The autoethnographic journey of athlete-centred experiences, research and learning : athlete to researcher, now coach, and beyond -- Athlete-centred coaching in swimming : an autoethnography -- Athlete-centred approach - beginning the process in junior teams -- Coach educators as athlete-centred practitioners -- Applying the game sense approach and Mosston and Ashworth's inclusion style-E to promote athlete-centred tennis coaching with junior novice players -- Athlete-centred coaching : tensions and opportunities arising in the masters context.
Includes bibliographical references and index.
Keywords: Coaching (Athletics); Athletes -- Training of